Limited Attention in Case-Based Belief Formation - Jörg Bleile (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
An agent wants to derive her belief over outcomes based on past observations collected in her database (memory). There is well establish evidence in the psychology and marketing literature that agents consistently fail (or choose not) to process all available information. An agent might be constraint to pay attention (recall) and consider only parts of her potentially available information due to unawareness, cognitive or psychological limitations or intentionally for effort-efficiency. Based on this insight, we axiomatize a two-stage belief formation process in which in a first step agents filter ((un)intentionally) the available information. In a second step individuals employ the remaining observations to express a belief. We impose cognitively and normatively desirable properties on the filtering process. The axioms on the belief formation stage describe the relationship between databases and their induced beliefs. The axiomatized belief induced by a filtered databases is representable by a similarity weighted average of the estimations induced by each past attentiongrabbing observation. An appealing application is a satisficing filter that induces a filtered belief that relies only on past experiences that are sufficiently relevant for a current problem. For the specific situation that agents (are able to) always pay attention to all available information, our axiomatization coincides with the axiomatization of a belief formation in Billot et al. (Econometrica (2005)).
Keywords: D01; D03; D11; D81; D83; 330; Belief formation; prior; case-based reasoning; relative frequencies; similarity; limited attention; consideration set; heuristics; satisficing; multicriteria choice; rationalization